2003
DOI: 10.1111/j.1096-0031.2003.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology versus molecules: resolution of the positions of Nymphalis, Polygonia, and related genera (Lepidoptera: Nymphalidae)

Abstract: The debate on whether to combine different data sets for simultaneous analysis has continued to the present day unabated. We have studied the effects of combining one morphological data set with four molecular data sets (two mitochondrial gene sequences and two nuclear gene sequences) for a group of butterflies belonging to the tribe Nymphalini using partitioned Bremer support. We particularly focus our attention on a group of species belonging to the genera Aglais, Inachis, Roddia, Nymphalis, Kaniska, and Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…), especially in elucidating the terminal relationships within individual lineages. Since morphological and molecular evidence are two autonomous sources of data for reconstructing phylogenies (Freudenstein et al, 2003), the confrontation and combination of different data matrices may corroborate or falsify the validity of the present results (see Vane-Wright, 2003;Wahlberg and Nylin, 2003).…”
Section: Phylogeny and Classification Of Maculinea And Glaucopsyche Smentioning
confidence: 62%
“…), especially in elucidating the terminal relationships within individual lineages. Since morphological and molecular evidence are two autonomous sources of data for reconstructing phylogenies (Freudenstein et al, 2003), the confrontation and combination of different data matrices may corroborate or falsify the validity of the present results (see Vane-Wright, 2003;Wahlberg and Nylin, 2003).…”
Section: Phylogeny and Classification Of Maculinea And Glaucopsyche Smentioning
confidence: 62%
“…In order to decide which species to contrast with each other we used phylogenetic information from recent molecular studies when available (Brunton 1998;Wahlberg and Zimmermann 2000;Zimmermann et al 2000;Wahlberg and Nylin 2003;Kandul et al 2004;Simonsen 2005;Weingartner et al 2006;U. Kodandaramaiah & N. Wahlberg, unpublished Coenonympha phylogeny), and in other cases we had to rely on traditional classification (Higgins 1975).…”
Section: General Methodologymentioning
confidence: 99%
“…Indeed, several authors (e.g. Sullivan, 1996;Baker et al, 1998;Carpenter and Wheeler, 1999;Baker and Gatesy, 2002;Edgecombe et al, 2002;Giribet et al, 2002;Meier and Wiegmann, 2002;Schulmeister et al, 2002;Stach and Turbeville, 2002;Lundberg and Bremer, 2003;Wahlberg and Nylin, 2003;Freitas and Brown, 2004;Wahlberg et al, 2005;Crowe et al, 2006;Bybee et al, 2008;Hermsen and Hendricks, 2008) have demonstrated the synergistic effects (e.g. increased levels of resolution and ⁄ or support of clades) of combining morphological and molecular data, and the contribution of these analyses for studies of classification, character evolution, and associating extant and fossil taxa.…”
Section: Separate and Combined Analysesmentioning
confidence: 99%